Multi-proxy analyses of sediment core OCE2022-KV02-GC - Dhanushka Devendra; Magdalena Łącka; Natalia Szymańska; Hasitha Nethupul; Joanna Pawłowska; Małgorzata Szymczak- Zyła; Magdalena Krajewska; Prasadi De Silva; Stein Bondevik; Steven J Gibbons (PANGAEA, 2025)
We present a multi-proxy dataset from sediment core OCE2022-KV02-GC, retrieved from the northwestern Barents Sea (74°50.296'N, 16°1.3403'E; 374 m water depth) during the AREX 2022 expedition aboard RV Oceania. The dataset includes oxygen stable isotopes (measured primarily on Elphidium clavatum), total organic carbon (TOC), grain size, X-ray fluorescence (XRF) data, biomarkers (alkenones and sterols), terrestrial DNA, and magnetic susceptibility. All proxy data are presented relative to core depth.